Digital Communication Actors In The Formation Of Artificial Intelligence Discourse On Tiktok: A Netnographic Analysis - Milda Nurrahmawati; Ahmad Tony (International Journal Of Humanities Education and Social Sciences (IJHESS), 2026)
The rapid popularization of Artificial Intelligence (AI) has extended beyond academic and industrial spaces into everyday social media discourse, with TikTok emerging as one of the most active arenas for AI-related public conversation. Although prior research has extensively examined TikTok’s algorithmic affordances and AI-related content circulation, limited attention has been given to the communicative roles of digital actors who actively shape public discourse on AI within TikTok’s participatory environment. This study examines how digital communication actors contribute to the formation, circulation, and reinforcement of AI discourse on TikTok through a qualitative netnographic approach. Data were collected from 45 publicly accessible TikTok videos published between May 2024 and June 2026, through non-participant observation using purposive quota sampling based on seven AI-related hashtags: #ArtificialIntelligence, #AI, #ChatGPT, #AITools, #AIIndonesia, #TeknologiAI, and #MachineLearning. Engagement metrics including likes, comment counts, and save counts were documented for each video. The analysis identifies five dominant communicative roles performed by digital actors: educators, opinion leaders, popularizers, critics, and amplifiers. Each role contributes distinct narrative framings of AI as a productivity tool, an economic opportunity, a threat to employment, an ethical concern, or a popular cultural trend. TikTok is positioned as an algorithmic digital public sphere where technological discourse is shaped through content formats, hashtag structures, visible engagement dynamics, and platform visibility mechanisms rather than unilaterally transmitted